2003
DOI: 10.1086/378188
|View full text |Cite
|
Sign up to set email alerts
|

H Line Polarization in the Major Flare of 2002 July 23. I. Observations and Data Analysis

Abstract: On 2002 July 23, a major 2B/X4.8-class flare was observed in Ha lines with the Large Solar Vacuum Telescope of the Baikal Astrophysical Observatory using the spectropolarimetric method. Linear polarization of 3%-10% has been detected in Ha lines of the flare, particularly in the Ha lines with a central reversal. They are mainly radial on the solar disk and appear at the impulsive phase of hard X-ray and g-ray bursts. The polarization changes its direction in a spatially limited small region (∼4Љ-5Љ) and within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These measurements will provide information on the electron anisotropy. Such studies, together with other measurements (i.e., radio imaging and spectroscopy [White et al 2003] and with optical [Firstova, Xu, & Fang 2003] polarization) will provide further constraints on the processes of energy release and particle acceleration in flares. 1 j) of the 300-500 and 700-1400 keV bands, respectively, dominated by bremsstrahlung emission.…”
Section: Gamma-ray Line Emissionmentioning
confidence: 99%
“…These measurements will provide information on the electron anisotropy. Such studies, together with other measurements (i.e., radio imaging and spectroscopy [White et al 2003] and with optical [Firstova, Xu, & Fang 2003] polarization) will provide further constraints on the processes of energy release and particle acceleration in flares. 1 j) of the 300-500 and 700-1400 keV bands, respectively, dominated by bremsstrahlung emission.…”
Section: Gamma-ray Line Emissionmentioning
confidence: 99%
“…The H α spectral observations of this flare also revealed the mustaches with a strong line inversion [ Firstova et al , 2003] observed at 0032:00 UT, just after the second maximum in hard X‐rays, in the location of hard X‐ray foot point B according to their slit position. The linear polarization of 3–10% with the plane of polarization parallel to the solar center direction is attributed to impact polarization that clearly indicates the presence of fast electrons propagating into the X‐ray B foot point located in the eastern ribbon where the slit was placed.…”
Section: Description Of the Datamentioning
confidence: 78%
“…There are also other indications for the presence of high‐energy electrons at the location of the source C, in the H α spectral observations of this flare, which revealed the mustaches appearing at 0032 UT just after the maximum in hard X‐ray emission in the location of the foot point C according to a slit position [ Firstova et al , 2003, Figure 1]. The H α line at these locations had a strong line inversion, its linear polarization was about 3–10% with the plane of polarization parallel to the solar center direction.…”
Section: Observed Magnetic Field Variationsmentioning
confidence: 99%
“…According to various authors, Hα and Hβ lines are linearly polarized in solar flares (Hénoux & Semel 1981;Metcalf et al 1992Metcalf et al , 1994Vogt & Hénoux 1996Firstova et al 1997Firstova et al , 2003Firstova et al , 2005Vogt et al 2001;Firstova & Kashapova 2002;Hénoux & Karlický 2003;Hanaoka 2003;Xu et al 2005). On the other hand, Bianda et al (2005), using the ZIMPOL instrument, and Hanaoka (2005) did not find any linear polarization signature in solar flares above a sensitivity level of 0.1%.…”
Section: Introductionmentioning
confidence: 96%